Compartmentalization of the periplasmic space at division sites in gram-negative bacteria. - Cook, W R (1986)
Phase-contrast and serial-section electron microscopy were used to study the patterns of localized plasmolysis that occur when cells of Salmonella typhimurium and Escherichia coli are exposed to hypertonic solutions of sucrose. In dividing cells the nascent septum was flanked by localized regions of periseptal plasmolysis. In randomly growing populations, plasmolysis bays that were not associated with septal ingrowth were clustered at the midpoint of the cell and at 1/4 and 3/4 cell lengths. The localized regions of plasmolysis were limited by continuous zones of adhesion that resembled the periseptal annular adhesion zones described previously in lkyD mutants of S. typhimurium (T. J. MacAlister, B. MacDonald, and L. I. Rothfield, Proc. Natl. Acad. Sci. USA 80:1372-1376, 1983). When cell division was blocked by growing divC(Ts) cells at elevated temperatures, the localized regions of plasmolysis were clustered along the aseptate filaments at positions that corresponded to sites where septum formation occurred when cell division was permitted to resume by a shift back to the permissive temperature. Taken together the results are consistent with a model in which extended zones of adhesion define localized compartments within the periplasmic space, predominantly located at future sites of cell division.